2012
DOI: 10.1080/0376835x.2012.715438
|View full text |Cite
|
Sign up to set email alerts
|

Small farms and sustainable rural development for food security: The Brazilian experience

Abstract: In the past few years, Brazil has made significant progress in reducing hunger and food and nutrition insecurity. By the end of 2009 it had met the first United Nations Millennium Development Goal of reducing poverty and malnutrition by half, six years ahead of the 2015 deadline. Much of this progress has been achieved through innovative policies and initiatives championed by civil society organisations for over two decades. This paper reviews some of the most important policies and initiatives which are havin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 11 publications
0
41
0
8
Order By: Relevance
“…It is estimated that smallholders and family farmers are responsible for about 70% of the food consumed in the country [48][49][50]. Analyzing 2006 AgCS data on the distribution of vegetable-producing properties and the amount of vegetables typically produced, according to the producer's land tenure status, we found that even producers who are classified as landless farmers contribute significantly to vegetable production, especially cassava, despite their lower stability, security, and access to financial resources.…”
Section: The Role Of Small Farming In Vegetable Productionmentioning
confidence: 99%
“…It is estimated that smallholders and family farmers are responsible for about 70% of the food consumed in the country [48][49][50]. Analyzing 2006 AgCS data on the distribution of vegetable-producing properties and the amount of vegetables typically produced, according to the producer's land tenure status, we found that even producers who are classified as landless farmers contribute significantly to vegetable production, especially cassava, despite their lower stability, security, and access to financial resources.…”
Section: The Role Of Small Farming In Vegetable Productionmentioning
confidence: 99%
“…In addition to the established four aspects of food security (FAO 1996), and in connection with the institutional framework and governance of food, the Ryerson University Centre for Studies in Food Security (2016: http://www. ryerson.ca/foodsecurity/our-approach/) adds a fifth dimension of food security, namely "agency," which multiple examples and cases point to as the most crucial critical factor for all aspects of food security (see also Chappell and LaValle 2011;Chappell 2017;and Rocha, Burlandy, and Renato 2012), and which highlight equity as an important pillar of agroecological food systems. This also links to "nourishment" as a concept which goes far beyond "providing passive populations with calories," focusing instead on peoples' ability, access and right to grow, exchange, and eat healthy, nutritious food which is meaningful to them, in a fair and equitable way (as, e.g., described in AFSA 2016).…”
Section: The Concept Of Agroecologymentioning
confidence: 99%
“…In large parts of Europe and North America, current farming practices have focused on very few types of production with only one yearly harvest of, for example, grain. Many exciting initiatives could serve as examples of urban food strategies involving local food producing systems (Sonnino 2016), and emerging agroecological food systems, viewing rural-urban landscapes as interconnected, and connecting actors through exchange of food and resources (Chappell 2017;Cohen and Ilieva 2015;Dubbeling 2013;FAO 2014a;Hummel et al 2015;Rocha, Burlandy, and Renato 2012;RUAF 2015;Getz Escudero 2014a, 2014b). The visions and practical organization shown in these examples bridge rather than contrast "rural" and "urban," which opens opportunities for sustainable, agroecological food systems across the rural-urban continuum (Forster and Getz Escudero 2014b), which again highlight the importance of contextuality, where smaller towns provide completely different options and challenges than larger cities, seen as contexts for city-region food systems.…”
Section: Contextuality Equity and Nourishment For Health Resiliencementioning
confidence: 99%
“…Roberto Rodrigues, a leading figure in Brazilian agribusiness, became the Minister for Agriculture, while the Ministry for Agrarian Development and its various subdivisions were shared out among allied parties, social movements, and trade unions. A further Ministry, that of Social Development and the Struggle against Hunger (MDS), was created to deal with this central policy of Lula's first Presidential term (Rocha, Burlandy, & Maluf, 2012). Later a special Secretariat (SENAES) would be created within the Ministry of Labor and headed by the renowned academic Paulo Singer to promote the Solidary Economy (Economia Solidária), a movement which in Brazil has a strong overlap with Fair Trade both in terms of its leading cadre and best organized producer groups, particularly in the rural context.…”
Section: The Shift Back To Commodities Food Security and Public Promentioning
confidence: 99%